Pengaruh Kapabilitas Teknologi Informasi Terhadap Kinerja dan Nilai Perusahaan - Rita Rahayu; Silfia Riski; Verni Juita (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The main objective of this study is to investigate the impact of information technology (IT) capabilities on firm performance and firm value. In this study the firm performance is measured by ROA and ROS, while the firm value is measured by Tobins Q. The matched sample comparison method is used to select the sample. In this regard, there are two groups of sample, which are the firms with superior IT capabilities and the firms that have not superior IT capabilities (as a control group). The firms that have been awarded by TOP IT & Telco Award were classified as the firm with superior IT capabilities. By using independent t test, it is found that there is no difference in firm performance and firm value between the firms with superior IT capabilities and the firms in control group. Therefore, it is found that there is no relationship between IT capabilities and firm performance and firm value